Design and development of liquid handling device at FKP - Nur Hafiza Iryani, Zahanapi (2013)
Liquid handling device (LHD) is a prototype system that can be used in FKP laboratory to transfer liquid substances from the main tank to other containers. Based on the concept, this study is aimed to develop a liquid device that have multifunction, which are transferring liquid substances to other containers manually and can refill the liquid from other source into tank automatically. The LHD has leveling system, using ultrasonic sensor which is used to state the balance of liquid in the tank, and in the refilling process, it helps to control the process where it stops the process automatically when the maximum level is reached. Single-stage DC pump is used to pump in and out liquid substances from the tank. The liquid-crystal display (LCD) informs the users about the balance of the liquid in tank. Indicators are used to trigger display warning about the process running by the device. There are three phases in this project. Phase I is designing system. Phase II covers the programming. The programming is built using Arduino IDE using C language. Phase III is building circuit and hardware, including the piping system. Pump, ultrasonic sensor, LCD, indicators and switches are connected at the Arduino board (microcontroller ATmega328). The system is validated by running 3 types of experiments to obtain and compare the time taken and speed of the Castrol Cooledge BI and Shell Tellus 68 between LHD and rotary hand drum pump (RHDP), experiment to obtain speed and volume of liquid obtained by RHDP by its revolution and efficiency test for refilling process using Cooledge Bi. The result shows speed of LHD is 16.68% slower than RHDP in pumping Cooledge BI out from the tank and speed of LHD is 81.74% slower than RHDP in pumping Tellus 68. Both of the situations happen due to low voltage of pump in the device and LHD need to use higher voltage pump to produce more speed and reduce more time. Based on the result, the selection of the pimp must be improvised to make the handling liquid device suitable to be implemented in the FKP lab.